ROLE OF MEDIA IN INDIAN DEMOCRACY - Magadum, Santosh (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Without media or free press a majority rules system can't find true success. In basic words a majority rules system is the public authority of individuals, for individuals and by individuals. In this sense for the dynamic and cautious cooperation of free press is fundamental in a vote based society. It is voice of individuals. It assumes a significant part in the molding of a sound majority rules government. Media is viewed as a heart of a vote based system society. As a significant wellspring of data it mindful individuals in all nations of the world. The media is for the most part thought to be as fourth mainstay of a majority rule government. It makes individuals aware of various happenings from grounds like games, legislative issues, financial, and social, and so forth. Media resembles a mirror likewise which delineations the essential reality and some of the time it very well might be brutal. The current paper is an endeavor to look at the job of media in Indian majority rules system since seventeenth hundred years, press is being perceived as Media of a majority rules government and a gathering for public conversation and discussion. Today, Media is regarded as guard dog, as a watchman of the public interest. Media associations are for the most part expected to assume a significant part in popular governments, yet how successful are they in carrying out this role involves study. The force of Media can be utilized to build up majority rules government. It very well may be utilized as an instrument to bridge among lead representatives and the administered. This Paper expects to investigation two separate parts of media execution: the degree to which they play out a 'guard dog' job by giving data, and how much they go about as a delegate discussion for the perspectives on residents. Through his exploration paper an endeavor has been made to feature the job of Media in fortifying majority rule government in India. The current review features the effect of media as a foundation of country working through political, social, financial and social vote based system.